Indonesias Higher Education: Context, Policy, And Perspective - Kyrychenko, Volodymyr (Asian Journal of Contemporary Education, 2018)
The paper focuses on the current situation and domestic context of Indonesia’s higher education system. It introduces trends, goals, and policies the government has issued to narrow the gap between domestic economic development and the challenges brought about by globalization. The author analyses the results the state has achieved as of today and examines problematic issues the country needs to pay attention to so that, the result, will bring Indonesia the desirable outcomes. This paper concentrates on a set of questions such as: What is the current higher education situation in Indonesia? What is the country’s capacity to change its policy and to open-up? How does it relate to more general notions of Indonesia’s education in the global perspective as well as from the perspective of the new-world-order? What are the main challenges? What is the plan of the Indonesian government to achieve educational goals?